(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
This study investigated the seasonal variation in groundwater quality across two major industrial areas, Sharada and Bompai, in Kano State, Northwestern Nigeria, over a twelve-month period from December 2023 to November 2024. The aim was to evaluate the extent, pattern, and temporal dynamics of groundwater contamination associated with industrial and anthropogenic activities during wet and dry seasons. Groundwater samples were collected from eight wells in Sharada and eight boreholes in Bompai. Selected water quality parameters were analysed using standard methods, including temperature, pH, electrical conductivity (EC), total dissolved solids (TDS), nitrate, sulphate, bicarbonate, chloride, and phosphate. Results revealed that pH ranged from 5.25 to 7.44, dropping below the WHO minimum guideline of 6.5 during April–May (pre-monsoon dry season). EC peaked at 2,090 µS/cm and TDS at 1,207 mg/L in May, exceeding the recommended limits of 0.7 dS/m and 500 mg/L, respectively. Nitrate reached 194 mg/L in December, while chloride peaked at 14,239 mg/L in June, indicating the influence of both industrial and agricultural sources. These findings identify April–May and December–January as critical periods for targeted groundwater quality management. It is concluded that groundwater quality in the study areas exhibits seasonal deterioration, with several parameters surpassing WHO standards during dry months. It is recommended that regulatory agencies intensify monitoring efforts and enforce pollution control measures during these high-risk periods to ensure safe and sustainable groundwater use.